2020
DOI: 10.3390/ma13163579
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Thermal-Protective Performance of Fire-Retardant Fabrics Considering Garment Aperture Structures Exposed to Flames

Abstract: The application of fire-retardant fabrics is essential for providing thermal protective function of the garments. Appropriate clothing design are beneficial for preventing the wearers from skin burn injuries and heat strains simultaneously. The intention of this work was to investigate the effects of clothing ventilation designs on its thermal protective performance by bench-scale tests. Four boundary conditions were designed to simulate the garment aperture structures on fabric level. Tests of thermal shrinka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Thus, increasing the under-clothing airflow velocity may play a relatively small role in positive thermal protection. 20 When the air-gap thickness increases, forced convection intensifies the heat transfer, accelerating the heating and increasing the temperature rise value. In the present study, at a 1 m/s flow rate, the impact of the under-clothing airflow on the heat diffusion simultaneously reduced the external heat, thereby yielding the strongest thermal protection.…”
Section: Effect Of Under-clothing Airflow On Fabricsystem Tppmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, increasing the under-clothing airflow velocity may play a relatively small role in positive thermal protection. 20 When the air-gap thickness increases, forced convection intensifies the heat transfer, accelerating the heating and increasing the temperature rise value. In the present study, at a 1 m/s flow rate, the impact of the under-clothing airflow on the heat diffusion simultaneously reduced the external heat, thereby yielding the strongest thermal protection.…”
Section: Effect Of Under-clothing Airflow On Fabricsystem Tppmentioning
confidence: 99%
“…Among them, Deng et al, 16 reported that fabric away from the garment opening has higher tensile strength retention following continuous heat exposure. Further, Tian et al, 20 noted greater fabric thermal shrinkage in the case of an open air‐gap boundary, along with superior TPP. Wang and Li 17 reported a higher degradation rate for the outer‐shell mechanical properties for the human motion states compared to the stationary state.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that heat is mainly transferred to the skin through heat conduction and radiation when the air gap is less than 6.4 mm for a sealed air gap. 10,[23][24][25] Since the thermal conductivity of the air was approximately 1/10th of that of the fiber, more heat was stored on the surface of the fabric, which led to the fabric heating up earlier and reaching a steady-state sooner. 20 In the steady-state, the heat absorbed by the fabric and the heat dispersed into the air gap were roughly equal.…”
Section: Temperature Evolution Of the Fabricmentioning
confidence: 99%
“…There was a significant difference in the surface area retention of the fabric between the sealed and open boundary air gaps. 10 When there was an air gap between the fabric and the human skin, or the side boundary of the air gap was open, the thermal shrinkage of the fabric was aggravated, and shrinkage occurred earlier. Therefore, the existence of the air gap aggravates the thermal degradation of the fabric to some extent.…”
mentioning
confidence: 99%
“…Thermal protective clothing is widely used in the manufacture of fire service uniforms and high-temperature working uniforms to protect firefighters or industrial workers from thermal hazards by providing insulation against heat transmission to human skin. 13 The firefighting suit is designed as a multi-layer structure, including an outer shell, moisture barrier, and a thermal liner, all of which are flame-retardant. Various standards clearly specify the minimum requirements for the performance of firefighting clothing; however, there are no clear guidelines for its continuous use.…”
mentioning
confidence: 99%